THE CONSTRUCTION OF FREEDOM IN A NOVEL "VEIL OF ROSES" BY LAURA FITZGERALD - Gelar Pratama Tresnadi, - (2010)
Entitled The Construction of Freedom in a novel Veil of Roses by Laura Fitzgerald, An Existentialist Feminism Analysis, the present paper endeavors to conduct the textual analysis of freedom issues in the novel Veil of Roses framed by Existentialist feminism. The analysis is directed to unveil the construction of freedom as evidenced in the text employing a descriptive qualitative method. Based on the findings, it is revealed that freedom is constructed upon the comparison between the main woman character's life in Iran and America. The comparison creates new conception of freedom for the main woman character. The woman character also enacted the principles of existentialist feminism which shows that woman can be whatever she wants to be, woman does not have to follow the identity that already constructed by man society, in this case patriarchal society, woman can engage in positive action in society, and woman can redefine or abolish her role as a wife, mother, and career woman.